Revisiting mobility: capital, labor and subjectivation - Leite, Ana Carolina Gonçalves; Giavarotti, Daniel Manzione; Kluck, Erick Gabriel; Boechat, Cássio Arruda; Toledo, Carlos de Almeida (Geografares, 2017)
From 1990s reviews of theoretical perspectives on migratory studies we here propose an analysis and a critique of one of them. With this paper, we highlight the decisive contributions of the theory of the labor mobility enabling to question the separation between the structural determinations claimed by the so-called historical-structural approach and the subjective will claimed by the neoclassic approach, besides the role performed by the discourses over migration and the mechanisms played by them as forms of controlling the space, the labor and the worker. However, we aim at moving the controversy further by proposing a critical reading of this very perspective in order to reveal its limits concerning the ontological conceptualization of labor in which its stands. Finally, we reflect upon the contemporary critical conditions of labor mobility and upon the position of crisis administration undertaken by the State planning together with the scientific production that supports it, what makes essential the critique even of those subjects who produce migratory studies.Keywords: Mobility of Labor; Critique of Labor; Fetishism.